2005
DOI: 10.1073/pnas.0503590102
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles for cholesterol in mammalian cells

Abstract: The structural features of sterols required to support mammalian cell growth have not been fully defined. Here, we use mutant CHO cells that synthesize only small amounts of cholesterol to test the capacity of various sterols to support growth. Sterols with minor modifications of the side chain (e.g., campesterol, ␤-sitosterol, and desmosterol) supported long-term growth of mutant cells, but sterols with more complex modifications of the side chain, the sterol nucleus, or the 3-hydroxy group did not. After 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 40 publications
2
105
0
Order By: Relevance
“…It is assumed that the reaction catalysed by SQLE is the rate limiting step in cholesterol biosynthesis, in post-HMG CoA regulation (Astruc et al, 1977;Tabacik et al, 1981). This is supported by the fact that cell growth inhibited by a specific SQLE inhibitor (NB-598) could be rescued by small amounts of cholesterol added to the culture medium (Xu et al, 2005).…”
Section: Discussionmentioning
confidence: 62%
“…It is assumed that the reaction catalysed by SQLE is the rate limiting step in cholesterol biosynthesis, in post-HMG CoA regulation (Astruc et al, 1977;Tabacik et al, 1981). This is supported by the fact that cell growth inhibited by a specific SQLE inhibitor (NB-598) could be rescued by small amounts of cholesterol added to the culture medium (Xu et al, 2005).…”
Section: Discussionmentioning
confidence: 62%
“…This could be due to the very similar chemical structures of both the sterols. Xu et al [29] have demonstrated that desmosterol may efficiently replace cholesterol in the cell membrane without compromising the functional properties because there are compensatory changes in membrane composition.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, it is an important structural component of cellular membranes, precursor of oxysterols, steroid hormones and bile acids. It regulates embryogenesis and development (Xu et al , 2005 ). Cellular cholesterol is strictly controlled by multiple pathways (Chang et al , 2006 ;Goldstein et al , 2006 ).…”
Section: Resultsmentioning
confidence: 99%